Perlindungan Hukum Terhadap Investor Online Ditinjau Dari Undang-Undang Nomor 25 Tahun 2007 Tentang Penanaman Modal - Poetri Enindah Suradinata; Jaya Setiawan Sinaga; Muh. Ardiansya S. (Jurnal Restorative Justice, 2023)
The digital economy's development changes how people invest by using internet facilities. Investments made online are circulating in the community with the lure of large profits without knowing the consequences that will be caused to investors. So investors need protection in investing online to avoid the risk of loss. This study aims to understand online investors’ position in conducting investment activities in Indonesia and how the form of legal protection for online investor losses according to Law number 25 of 2007 concerning Investment. Research using normative juridical methods, namely literature research. Then data collection through legislation, books, journals, court decisions, and research results are analyzed qualitatively and presented descriptively. From the results of the research conducted, the position of online investors in conducting investment activities in Indonesia is the same as other investors mentioned in Article 1 number 4 of Law 25/2007. Then the form of legal protection for online investor losses is contained in Porigin 14 letter (a) of Law 25/2007 in the form of guarantees of provided repressively for disputes in the field of investment for investors as capital owners of legal rights and interests as a form of guarantee provided by the state.